Doing the right thing for one's children: deciding whether to take the genetic test for Huntington's disease as a moral dilemma. (21st March 2013) - Smith, JA; Stephenson, M; Jacobs, C; Quarrell, O
<x xml:space="preserve">Abstract</x> This is a qualitative examination of candidates' decision‐making in relation to the genetic test for Huntington's disease. Semi‐structured interviews were conducted with nine participants who were asked about factors influencing their decision whether to take up predictive genetic testing. Transcripts of interviews were subjected to interpretative phenomenological analysis to elicit emergent themes. A key factor for participants was to do the right thing for their children. Interestingly, this factor presents a moral dilemma to participants and can direct them either towards or away from testing. This article offers a detailed examination of how participants think through this dilemma.